Results of Baseline Assessments of Two Viral Load and Early Infant Diagnosis Laboratories in Gaza Province, Mozambique. (11th September 2019) - Nhabomba, Augusto; Assane, Mariamo; Adamo, Noorbebi; Benzane, Octavia; Pinto, Isabel; Macave, Admiro; Basu, Debby; Landgraf, Kenneth
Abstract: Following the WHO 2013 recommendations for routine HIV viral load (VL) testing as the tool to monitor antiretroviral therapy, countries have prepared for massive testing scale-up. However, developing countries that also bear the highest HIV prevalence often lack qualified human resources and basic infrastructure. Mozambique has established 13 VL laboratories, including 2 in the province with the highest overall HIV prevalence, Gaza. The challenges to VL testing implementation and this rapid scale-up demand an urgent investment toward laboratory accreditation to ensure accurate and reliable VL results. To identify gaps and areas for improvement where additional resources may be needed to provide high-quality VL testing services, the CDC developed a VL and Early Infant Diagnosis (EID) scorecard (106 points; 5 levels). The scorecard evaluates 9 key areas, including (1) Personnel, (2) Facility/Environment, (3) Safety, (4) Procurement/Inventory, (5) Sample Management, (6) Equipment, (7) Process Control, (8) M&E Documents and Records, and (9) Internal Quality Audits/Quality Indicators. These 9 essential areas cover the pretesting, testing, and posttesting phases along the continuum of care for HIV patients. Baseline assessments in the two VL and EID laboratories in Gaza Province, Carmelo Molecular Laboratory and Xai-Xai Molecular Laboratory, were recently conducted. Personnel standards and M&E documentation represented strengths across both laboratories, with over 70% of the master list of M&E documents having been developed and in use. The overall gaps identified included poor segregation and prioritization of higher VL results (>1, 000 cp/mL), lack of internal audits, and no follow-up of nonconformities. Both laboratories scored in the level 2 range, with a total of 68 points (Carmelo) and 78 points (Xai-Xai). Considering this is a baseline assessment, we conclude that both labs are on an excellent path toward accreditation; however, additional laboratory quality mentorship is needed in order to reach accreditation standards.